Draft Evidence by the Nursing Advisory Committee of the Trades Union Congress on nursing conditions & recruitment
1938-03-02 1938 1930s 9 pages - 3 - working nurses themselves resulted in the following interesting result:- The principal drawbacks to the Profession were given as:- 1. Length of hours on duty. 2. Rates of pay for trained staff. 3. So-called petty restrictions. 4. Lectures in off duty hours. 5. Limited prospects of advancement. 6. Non-interchangeability of Pensions. 7. Living in. 8. Gap between school and hospital. We propose to comment upon these together with other reforms that we suggest. 9. Hours of Duty. The Trades Union Congress draws the attention of the Committee to the fact that they have on several occasions promoted a Local Authorities (Hours of Employment in connection with Hospitals and Institutions) Bill which has twice been before the present House of Commons. The second reading (3rd December, 1937) was defeated by a majority of 11 votes (122 to 111) after debate in which the balance was distinctly in favour of the Bill. 10. In our opinion the Nursing Profession has got to face up to the fact that working hours in all trades and professions are becoming progressively shorter, and that as other professions improve their conditions, the position of the Profession will become much worse than it is at the present time. 11. We recognise that during the past two or three years several hospitals have introduced a 48 hour week or 96 hour fortnight, and we note with interest that The Bulletin issued by the American Nurses Association reports that several of the difficulties which are experienced in securing Nurses in that country have been removed since the introduction of the 8 hour day. Overtime. 12. The Bill introduced in the House of Commons provides for the payment for overtime worked in excess of 96 hours in a fortnight, and we lay special value on this provision although we recognise that many senior Nursing Officers regard it as undignified. It is our experience that the payment of overtime is a distinct curb on inefficient administration, that it lessens the amount of overtime worked and provides some compensation for the additional fatigue incurred. Salaries. 13. It is admitted that some improvement in salary scales has been seen during the past 5 years, due to 292/54.73/2/18-22